Application of the Movement Method in Efforts to Improve Memorization of Hadith in the Hadith - Isra Hayati; Nurul Zahrianti Jf; Juita Rahmadani Manik (CERED Indonesia Institute, 2021)
The background of the application of the movement method for memorizing hadi? in Tadika with focus on memorizing hadi? for group B children. Data collection conducted by observation, interviews, and documentation. This research is background backed by the activities of memorizing hadi? which are often carried out by schools and teachers use the lecture method and assign students to memorize ?adi?. So that the child looks passive and the learning atmosphere is not conducive. During the apperception in the next lesson, many children have forgotten, only a few children are still able to remember the ?adi? they have learned. The results showed that: Application of the movement method for memorizing ?adi? in children in Tadika, Malaysia. Second, the implementation of activities memorize ?adi? at first done at home without movement and done at school with hand symbol movements with classical activities, the third evaluation ?adi? memorizing activities in the form of level of attainment and follow-up will be reported to parents during the meeting of the two end of the theme. Factor support in applying the movement method to memorize ?adi? on Tadika Among others: handouts for parents, children's interests, self-confidence, class atmosphere which is conducive, and a manual of movement methods for memorizing ?adi?. Factor obstacles in memorizing ?adi? with the movement method, namely: style children's learning, children's memory, teacher's ability and lack of training to parents regarding the method of movement to memorize ?adi?, no pictures full color, and ?adi? is not equipped with asbabul wurud